Sustainability assessment of geopolymer concrete synthesized by slag and corncob ash. (December 2022) - Oyebisi, Solomon; Olutoge, Festus; Kathirvel, Parthiban; Oyaotuderekumor, Increase; Lawanson, David; Nwani, Joy; Ede, Anthony; Kaze, Rodrigue
Abstract: Globally, sustainable construction materials are promoted in the construction and building sector due to the high utilization of Portland cement as a conventional binder and its associated energy and environmental impacts. Consequently, geopolymer concrete emerges as a substitute for conventional concrete. This study designed two grades of geopolymer concrete (GPC) strengths (C 30 and 40 MPa) with ground granulated blast furnace slag (GGBFS) and corncob ash (CCA) as alternative binders. The binders, varied at 0–100 wt% of GGBFS by CCA, were activated with sodium hydroxide (SH) and sodium silicate (SS) solutions. After 28 days of curing, the compressive strength of the concrete cubes was determined. Furthermore, the environmental impacts of the concrete constituents were assessed. At the same time, their sustainability and economic indexes were estimated via the Inventory of Carbon and Energy (ICE) within the cradle-to-site confinement. The findings showed that GGBFS-CCA-based geopolymer concrete exhibited lesser environmental impact and higher sustainable and economic efficiency than Portland cement concrete. Thus, these outcomes can be advantageous in achieving a cleaner built milieu and sustainable construction. Highlights: Embodied energy of slag-ash-based geopolymer concrete reduces with increasing concrete grade strength. Slag-ash-based geopolymer concrete offers a potential saving on global warming potentials. Slag-ash-based geopolymer concrete provides a potential saving on global temperature potential. The sustainability efficiency of slag-ash-based geopolymer concrete increases with increasing ash content. The economic viability of slag-ash-based geopolymer concrete increases with increasing concrete grade strength.